Radical cystectomy and urinary diversion in women: techniques, outcomes, and challenges-a narrative review - von Deimling, Markus; Laukhtina, Ekaterina; Pradere, Benjamin; Pallauf, Maximilian; Klemm, Jakob; Fisch, Margit; Shariat, Shahrokh F; Rink, Michael (Translational andrology and urology, 2022)
BACKGROUND AND OBJECTIVE: Standard radical cystectomy (RC) in women includes the removal of the bladder, urethra, uterus with the adnexa, and the anterior vaginal wall, thereby severely affecting the urinary, sexual, and reproductive system. To limit these detrimental effects, organ-sparing, including nerve-sparing approaches, have been developed. Health-related quality of life (HRQOL) and functional outcomes are, indeed, becoming increasingly central to the shared decision-making with the patient. The objectives of this narrative review are: (I) to review the current status of RC in women, including the use of different urinary diversions (UDs); (II) to discuss organ-sparing approaches and their impact on oncological and functional outcomes in women; (III) to discuss the impact of RC on HRQOL and sexual function in women. METHODS: We performed a non-systematic literature review of the available publications in the PubMed database. KEY CONTENT AND FINDINGS: Over the past years, gender differences in oncological and functional outcomes after RC have received increased attention. According to the currently available literature, organ-sparing approaches can be safely performed in well-selected women without negatively impacting oncological outcomes. The orthotopic neobladder is feasible and oncologically safe in well-selected and informed women. The choice of the UD should be based on comprehensive counseling and the patient's comorbidities and preferences. There still is a lack of data on sexual recovery after the different surgical approaches aimed to mitigate sexual dysfunction in women undergoing RC. CONCLUSIONS: Pre-and post-operative counseling and support of females undergoing RC regarding their expectations and experiences in terms of quality of life and functional and sexual outcomes are currently insufficient. Well-designed studies in this field are necessary to further improve outcomes of women treated with RC with an overarching aim to close the gender gap in managing women with bladder cancer.